La promoción de la democracia en América Latina - Perina, Rubén M. (Estudios Internacionales, 1993)
This paper is a review of Thomas Carothers' work on the Reagan administration's policy towards Latin America and his contribution to the democratization of the region (In the Name of Democracy. U.S. Policy Towards Latin America in the Reagan Years). What the book raises about political assistance and democracy promotion programs is mainly criticized. Reference is made to this matter highlighting the importance and validity of this type of programs. It is argued that although these point to formal aspects of democracy, they influence a series of other factors that effectively help its establishment and consolidation.